2005
DOI: 10.1136/thx.2004.027532
|View full text |Cite
|
Sign up to set email alerts
|

Association between short term exposure to fine particulate matter and heart rate variability in older subjects with and without heart disease

Abstract: Background: Short term increases in exposure to particulate matter (PM) air pollution are associated with increased cardiovascular morbidity and mortality. The mechanism behind this effect is unclear, although changes in autonomic control have been observed. It was hypothesised that increases in fine PM measured at the subjects' home in the preceding hour would be associated with decreased high frequency heart rate variability (HF-HRV) in individuals with pre-existing cardiac disease. Methods: Two hundred and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 36 publications
1
30
0
1
Order By: Relevance
“…Additionally, more than two dozen human exposure studies (Michaels and Kleinman, 2000) and several animal studies offer evidence for PM-mediated health effects at time scales shorter than 24 h. For example, acute pulmonary inflammation (latency period 6 h) has been observed in response to 1-h exposures to diesel exhaust (Salvi et al, 1999), and episodes of asthma have been found to correlate more strongly to 1-and 8-h PM 10 concentrations than to 24-h means (Delfino et al, 1998(Delfino et al, , 2002. Cardiovascular effects, such as reduced heart rate variability, of short-term human exposures to fine particles have also been investigated (Gold et al, 2000;Le Tertre et al, 2002;Sullivan et al, 2005). Resolving epidemiologic and dose-response relationships calls for finer temporal resolution of exposures.…”
Section: Indoor Air Quality In Rural Kitchens: a Public Health Prioritymentioning
confidence: 99%
“…Additionally, more than two dozen human exposure studies (Michaels and Kleinman, 2000) and several animal studies offer evidence for PM-mediated health effects at time scales shorter than 24 h. For example, acute pulmonary inflammation (latency period 6 h) has been observed in response to 1-h exposures to diesel exhaust (Salvi et al, 1999), and episodes of asthma have been found to correlate more strongly to 1-and 8-h PM 10 concentrations than to 24-h means (Delfino et al, 1998(Delfino et al, , 2002. Cardiovascular effects, such as reduced heart rate variability, of short-term human exposures to fine particles have also been investigated (Gold et al, 2000;Le Tertre et al, 2002;Sullivan et al, 2005). Resolving epidemiologic and dose-response relationships calls for finer temporal resolution of exposures.…”
Section: Indoor Air Quality In Rural Kitchens: a Public Health Prioritymentioning
confidence: 99%
“…Investigators have also proposed that the autonomic nervous system is a major player in the response to air pollution, largely bolstered by observational studies showing (though not consistently) decreases in heart rate variability which might reflect a tipping of autonomic balance in favor of sympathetic activation (9,10). But if this really occurs, is it an important phenomenon reflecting direct neurogenic response in the lung with resulting enhanced susceptibility to arrhythmic events, or again a downstream indication of a larger inflammatory phenomenon?…”
mentioning
confidence: 99%
“…45 While the majority of the studies point to a significant association of particle pollution with reduced HRV, effects of PM 2.5 on HRV have not been found in panel studies conducted in Northwestern US and Canada, perhaps because of differences in particle composition or, alternatively, low power. [46][47][48] Also, in contrast to the negative associations noted above, increases in traffic pollution were associated with increased HRV in a study of a younger healthy population of traffic police in North Carolina. 49 The investigators hypothesize that the nature of the pollution-related autonomic dysfunction may depend on the age and underlying disease states of the study participants.…”
Section: Discussionmentioning
confidence: 75%
“…This list of highly soluble elements includes three of the 375 seven HAPs discussed above, including the two (As and Cd) that are listed as carcinogens by the 376 U.S. EPA. 47 Conversely, fine particulate Al, Fe, and Sn were largely present in insoluble forms 377 at Steubenville; these elements had median fractional solubilities < 0.2. 378…”
Section: Source Apportionment 236mentioning
confidence: 99%